Speaking to Monuments and their Ghosts: Performance Art as Ephemeral Knowledge Sharing - Sutherland, Erin (Journal of Critical Race Inquiry)

(untitled) (Queen's University, 2025)
Talkin Back to Johnny Mac is a performance series that I curated in response to the 200th birthday celebrations for John A. Macdonald held in Kingston, Ontario in 2015. Many of the 2015 performances that examined and intervened in the Prime Minister’s ongoing memorialization took place at his statue in Kingston. In 2021, the statue was removed by the city after many requests from community members. I returned to the site of the statue in October 2025 with a new performance series in order to explore the ways in which the site had changed since the removal of the statue, and the ways in which it had stayed the same. This essay explores the performances by artists David Garneau, Leah Decter, Peter Morin and Jimmie Kilpatrick in 2015 and 2025 as a way to consider the colonial narratives that continue to be present at the site of the statue, and the ongoing importance of performance to create spaces for critical and community-oriented interventions.